Optimization in modal matching for correspondence of objects nodal points - Maria Luísa Ferreira dos Santos Bastos (2003)
The methodology presented in this paper, for the correspondence (matching) of two images objects nodal points, was previously developed and basically it consists in the construction of a matrix that relates the two objects nodal points, based in 1) geometric or 2) physical modelling. In the referred methodology, the matching is done by using a local search. To overcome this disadvantage, an application of global optimization techniques in the matching process is presented in this paper. Therefore, with this solution, the objects nodes interdependence is considered. It is also presented a new solution, applicable to contour objects, developed to adequately match the excess nodes (if they exist). This situation was not possible with the usual matching "one with one".